Understanding sport events organisational elements and impacts from the organiser and residents’ perspective - Chersulich Tomino, Ana; Perić, Marko (Hotel and Tourism Management, 2025)
Purpose – Sustainable sport tourism events require careful planning that considers all stakeholders’ needs to enhance benefits and reduce negative impacts. This study, based on data from 670 respondents in Poreč and Zagreb (Croatia, Europe), hosts of major triathlon and skiing events in 2022 and 2024, examines the relationship between event impacts and organisational elements from the perspectives of organisers and residents. Methodology – Exploratory factor analyses was used to identify the dimensions of the impact of events and organizational elements. T-tests were used to analyse differences between the perception of two groups of stakeholders, and Pearson’s correlations were used to identify links between the impact of events and organizational elements. Findings – Six dimensions of impact and three dimensions of organizational elements were identified, with event organizers and residents having different perceptions of these dimensions. There is a strong positive correlation between all three organizational elements and sociocultural, economic and reputational impacts, while environmental and safety principles, along with legacy planning, were mostly associated with organizational costs. Implications – Understanding these differing perceptions and their relationship to specific impacts can help organisers and policymakers develop more effective strategies to achieve sustainable outcomes.